Clinical Significance of Serum PGC-1 Alpha Levels in Diabetes Mellitus with Myocardial Infarction Patients and Reduced ROS-Oxidative Stress in Diabetes Mellitus with Myocardial Infarction Model - Zhu N (Dove Medical Press, 2020)
Ning Zhu, Xue Yan, Hongli Li, Huiqin Wang Department 1 of Cardiology, Baoding First Center Hospital, Baoding 071002, Hebei, People’s Republic of ChinaCorrespondence: Ning ZhuDepartment 1 of Cardiology, Baoding First Center Hospital, 320 Changchengbeidajie, Baoding 071002, Hebei, People’s Republic of ChinaTel +86-312-5096409Email zhuning_my@21cn.comBackground: In this study, we explored the clinical significance of serum peroxisome proliferator-activated receptor gamma co-activator 1 (PGC-1) alpha levels in diabetes mellitus with myocardial infarction (DMMI) patients and investigated the possible mechanism.Materials and Methods: Serum samples were obtained from patients with DMMI or normal volunteer in Baoding First Center Hospital. C57BL/6 mice were induced by a single intraperitoneal (i.p.) injection of 100 mg/kg STZ (streptozocin) for in vivo model. Human myocardial cell lines H9C2 cells were induced with high glucose medium (33 mmol/L glucose) for in vitro model. Western blot was used to analyze the protein expressions in this study.Results: Serum PGC-1 alpha levels were down-regulated in patients with DMMI. There was negative correlation between serum PGC-1 alpha levels and glycated hemoglobin, blood glucose or glucagon in DMMI patients. Recombination of PGC-1 alpha protein decreased the levels of glycated hemoglobin, blood glucose and glucagon, and inhibited oxidative stress and myocardial damage in mice of DMMI. Over-expression of PGC-1 alpha reduced reactive oxygen species (ROS)-oxidative stress, while down-regulation of PGC-1 alpha promoted ROS-oxidative stress via regulation of hemeoxygenase− 1 (HO-1) expression in in vitro model of DMMI. The inhibition of HO-1 expression attenuated the anti-oxidation effects of PGC-1 alpha in vitro.Conclusion: PGC-1 alpha attenuated ROS-oxidative stress in diabetic cardiomyopathy model, and PGC-1 alpha served as a potential intervention to alleviate DMMI in clinical applications.Keywords: PGC-1 alpha, ROS, oxidative stress, diabetes mellitus with myocardial infarction